The architecture of downtown Troy : an illustrated history - Waite, Diana S. (Excelsior Editions, State University of New York Press, 2019)
Located about 150 miles north of Manhattan, on the east bank of the Hudson River, the city of Troy, New York, was once an industrial giant. It led the nation in iron production throughout much of the nineteenth century, and its factories turned out bells and cast-iron stoves that were sold the world over. Its population was both enterprising and civic minded. Along with Troy?s economic success came the public, commercial, educational, residential, and religious buildings to prove it. Stores, banks, churches, firehouses, and schools, both modest and sophisticated, sprouted up in the latest architectural styles, creating a lively and fashionable downtown. Row houses and brownstones for the middle class and wealthy rivaled those in Brooklyn and Manhattan. This book tells the stories behind the many handsome and significant buildings in downtown Troy and how they were designed and constructed. For the first time in generations, scores of Troy buildings are again linked with their architects, some local but others from out of town (the?starchitects? of their day) and even from Europe. In addition to numerous historic images, the book also includes contemporary photographs by local photographer Gary Gold.